The Impact of Privatization on Achieving the Quality of Public Services in The Light of Islamic Management: أثر الخصخصة في تحقيق جودة الخدمات العامة في ضوء الإدارة الإسلامية - Abdullah Salim Al Junaibi, Said; Muwazir, Mohd Rizal; Khan, Issa (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2022)
This study aims to demonstrate the extent of privatization impact on achieving the service quality in production, performance and customer satisfaction in view of Islamic management. This study reflects the concern of Islam regarding the service quality and development and efficiency of products. The study importance is clear for demonstrating the privatization role in quality, efficiency, and improving production and marketing, to change the negative perception of privatization in the Arabic societies. This study adopted the inductive-analytical methodology for it conforms to the research nature and achieves its objectives. The study found many results. Privatization greatly contributes to attaining the quality of services in production and their performance with the best specifications and competitive prices, so that they achieve customer satisfaction and meet his current needs and future aspirations. The researcher recommends that research centres and academic authorities execute conferences dealing with the impact of privatization in achieving quality in all types of public services such as education, health, transportation, electricity, water, and others.